Using process approach to enhance writing ability of form three students of SMK Trolak (IR) - Mohd Mohathir Jamaludin (2005)
The main aim of this study was to find out whether process approach writing can be utilized as an effective approach in enhancing students writing ability. Furthermore, it was also the interest of this study to determine the students perceptions on the process approach writing. Data collected for this study were collected through students written drafts. The students were assessed using the pre-test and the post-test experimental research method. Results from both tests were analyzed using the t-test formula for the dependent samples. Twenty Form Three students of Sekolah Menengah kebangsaan Trolak, 35600, Sungkai, Perak were chosen to be the research samples. The samples were chosen at random. Research findings have shown that process approach writing has significant effects in enhancing writing skills among the students. In addition, the study also shows that process approach is able to attract students interest in producing better essays. Apart from that, the approach also helped to motivate the students to participate actively in the teaching and learning process. Findings of this study also reveal that various methods such as journal writing, peer-group editing and responding to different aspects of writing and students abilities are useful in ensuring smooth implementation of process approach writing.